TO THE QUESTION OF IMPROVING THE SYSTEM OF MANAGING WITH STATE CORPORATE RIGHTS - Radionova, N. V. (Science and Transport Progress, 2006)
The article considers the issues and main directions of improvement of the system of management of the state corporate rights in the present-day market conditions of Ukraine.